KADAR PENERIMA TRANSFERIN TERLARUT (sTFR) DI PENDERITA HIV/AIDS DENGAN ANEMIA - Indrati AR; Van Crevel R; Sumantri R; Wisaksana R (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Anemia is the most common hematologic abnormality associated with HIV which affecting 60 to 80 percent of patients in the latestage of the disease. The presence of anemia is associated with increased of morbidity and mortality in patients with HIV infection. Irondeficiency, chronic inflammation and antiretroviral treatment (ACT) may cause HIV associated anemia. The differentiation of irondeficiency anemia from chronic disease anemia is a diagnostic challenge. Maybe it is helpful in soluble transferrin receptor (sTfR), thecleaving of the extra cellular domain related to transferrin receptor. Because the elevated sTfR concentration is a marker of tissue irondeficiency and increased marrow erythropoietin activity. The aim of this study was to examine the diagnostic value of soluble transferrinreceptor level in anemia patients with HIV/AIDS. The Study was the part of the IMPACT (Integrated Management for Prevention, Controland Treatment of HIV/AIDS) baseline and cohort study. The study started since September 2007 in RSUP Hasan Sadikin Bandung.There were 179 HIV/AIDS patients with anemia included in this study. Complete blood count, reticulocytes, feritin, soluble transferringreceptor and hsCRP were tested in these patients. It was found that the mean of sTfR in HIV patients with anemia were 1238.42U/mL(304.5-30435). sTfR had a low correlation with MCV (r -0.174), feritin (r -0.65) and absolute reticulocyte counting (r 0.172). Feritinhad moderate and significant correlation with hsCRP (r:0.429; p 0.00). There was no significant difference of sTfR level between thepatients without ART, with Zidovudin and d4T (p 0.81). There was no significance difference of sTfR concentration between the low andnormal MCV level (p 0.341). sTfR can not differentiate the source of anemia in patients with HIV/AIDS. It can be concluded so far thatchronic disease and inflammation as reflected by the elevated hsCRP level and use of zidovudine are the main cause of anemia.